PD-1 Inhibitors in the Advanced Esophageal Cancer - Hong, Ye; Ding, Zhen-Yu (Frontiers in Pharmacology, 2019)
Esophageal cancer (EC) is a lethal disease, and ranks 7th in incidence and 6th in mortality worldwide. Patients are treated with surgery and/or chemoradiotherapy for a curative intent, but for those with advanced diseases systemic chemotherapy and targeted therapy are the mainstay treatment with poor prognosis. For the patients with squamous cell carcinoma and those progressed after chemotherapy, treatment option is even fewer, and effective treatment modalities are urgently needed. Preclinical and clinical studies have found the PD-1/PD-L1 inhibitors activate T lymphocytes, inhibit cancer growth, and improve survival in cancer patients. Multiple PD-1/PD-L1 inhibitors have been approved for the management of a variety cancers. Interestingly, a large of proportion of EC patients have tumors with PD-L1 expression and high tumor mutation burden. Trials have been performed to evaluate the efficacy and safety of the PD-1/PD-L1 inhibitors in EC patients. This review will summarize the current progress in this field, esp. the toxicities associated with these agents.